Islam in the balance : ideational threats in Arab politics - Rubin, Lawrence, 1973- (Stanford, California : Stanford Security Studies, an imprint of Stanford University Press, 2014)
This volume analyses how ideas, or political ideology, can threaten states and how states react to ideational threats. It examines the threat perception and policies of two Arab, Muslim majority states, Egypt and Saudi Arabia, in response to the rise and activities of two revolutionary 'Islamic states', established in Iran (1979) and Sudan (1989). The book has significant implications for international relations theory, including religion and international affairs, and engages important debates in comparative politics about authoritarianism and Islamic activism.
Introduction -- The ideational security dilemma, ideational power, and ideational balancing -- Ideational projection after the Iranian Revolution -- The power of a weak state : Sudan's relations with Saudi Arabia and Egypt -- Indirect power projection and ideational balancing after Khomeni -- Conclusion : balancing the Brotherhood.
Includes bibliographical references (pages 165-176) and index.
Print version record.
Master record variable field(s) change: 651
Keywords: Islam and politics -- Middle East; National security -- Middle East; Egypt -- Politics and government -- 1981-2011.; Saudi Arabia -- Politics and government -- 1982-; Iran -- Foreign public opinion, Arab; Sudan -- Foreign public opinion, Arab; Middle East -- Foreign relations -- 1979-; Middle East -- Politics and government -- 1979-; Threat (Psychology) -- Political aspects -- Middle East; International relations -- Psychological aspects; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; Electronic books